CITRA DIRI PROFESI ARSITEK DI MEDIA SOSIAL TIKTOK (Studi Kasus Personal Branding Ariq Naufal pada Akun @riqmann) - Pegary Paras Putri, (2022)
Ariq Naufal is an architect who also works as a content creator on TikTok. Through his content, Ariq Naufal provides information and education about architecture that is close to the lives of ordinary people. Therefore, this study seeks to explain more about the self-image of an architect on social media through the formation of personal branding that he does. The research method used in this study is a cultivative method that seeks to explore and explain the meaning that comes from a social problem, and uses a case study approach in which it seeks to develop and evaluate an in-depth analysis of a problem. Data collection techniques used in this study were observation and interviews. The researcher used four stages of data analysis belonging to Miles & Huberman whose contents were data collection, data reduction, data presentation, and conclusion drawing/verification. To analyze the personal branding built by Ariq on TikTok social media, the researcher uses Peter Montonya's eight personal branding concepts and a dramaturgical approach. The study found that Ariq had implemented the eight personal branding concepts on his TikTok account. Besides that, Ariq has also built a positive self-image, as an architect who shares information about architecture on TikTok.